ANALYSIS OF FACTORS INFLUENCE SMOKING BEHAVIOR IN POOR HOUSEHOLDS IN WEST SUMATERA PROVINCE - Hefrizal Handra, Hefrizal Handra; Zamzami, Zamzami (AFEBI Economic and Finance Review, 2016)
This research is purposed to learn the behaviors of poor households inmanaging their income for buying cigarettes using data from the National SocialEconomic Survey of West Sumatera Province in 2013 using OLS method as a toolof analysis.Results of the analysis show that the cigarette spending in percentage ofincome in smoker households in West Sumatera Province is very large, far largerthan the percentage of spending for education and health. Household cigarettespending is influenced by income factors, cigarette prices, number of adult malehousehold members, area of residence, age category of the household head, andeducation of the household head.